Synthesis and characterization of some new complexes of Co(II), Ni(II), Cu(II), Zn(II), Cd(II), Hg(II) with 2,3 and 3,4- di-(2΄-thiophenoyloxy) aniline - Saba M. Alasalli (College of Education for Pure Sciences, 2012)
Abstract A series of new complexes of the type [M(L1)Cl2] , [M(L2)Cl2] and [M΄(L1)(Th)2] where L1=2,3-di-(2΄-thiophenoyloxy) aniline, L2=3,4-di-(2΄-thiophenoyloxy)aniline, M=Co+2, Ni+2, Cu+2, Zn+2, Cd+2 and Hg+2, M΄= Ni+2, Cu+2, Zn+2 and Cd+2, Th=thiophene carboxylate. The complexes were prepared and characterized by molar conductance, IR, UV/vis spectra studies, magnetic measurements and metal content analysis. Conductivity data in DMF for complexes (1-12) and DMSO for complexes (13-16) showed that all complexes are non-electrolyte. Magnetic moment and electronic spectra indicate that some of the complexes contain a tetrahedral and the other have octahedral environment.